Lithology Identification Method for Marine–Continental Transitional Shale Systems Based on Superposition Reconstruction: A Case Study of the Shanxi Formation, Ordos Basin, China - Xinglei Song; Congjun Feng; Zhen Qiu; Sizhong Peng; Teng Li; Pengfei Wu; Zhiqiang Chen; Mengsi Sun (Natural Resources Research, 2026)

The sedimentary provenance of Upper Miocene Dongfang submarine fan, Yinggehai Basin: source-to-sink system unravelled through new detrital zircon U-Pb ages and heavy mineral analysis - Xingzong Yao; Congjun Feng; Wei Zhou; Pengfei Wu; Hongjun Qu; Jiahao Lei; Zhiqiang Chen; Yanlong Ge; Mengsi Sun (Marine and Petroleum Geology, 2025)

Source-to-sink processes and genetic mechanism of progradational and lateral accretion submarine fans in the Qiongdongnan Basin, South China Sea - Congjun Feng; Guozhang Fan; Zhili Yang; Xingzong Yao; Xinglei Song; Weiqiang Li; Hongjun Qu; Qiang Zhang; Xuefeng Wang (Frontiers in Marine Science, 2024)
Submarine fan reservoirs are important accumulation zones for oil, gas, and natural gas hydrates, offering significant potential for hydrocarbon exploration. During the deposition period of the Sanya Formation in the southern part of the Changchang Sag of the Qiongdongnan Basin, a large submarine fan developed. However, the internal structure, source-sink system, and formation mechanism of this fan remain poorly understood, posing significant challenges to exploration in this area. This paper examines the source-to-sink sedimentary processes and deposition of submarine fans, using the Changchang Sag, in the Qiongdongnan Basin in the Northern South China Sea, as an example, which will provide valuable general guidance for deep water oil and gas exploration. Based on the theories of seismic stratigraphy and seismic sedimentology, this paper utilizes techniques such as seismic facies analysis, seismic attribute optimization, paleogeomorphology reconstruction, and source-to-sink sedimentary system analysis to analyze the 3D seismic data of the study area. Research indicates that the Sanya Formation in the Changchang Sag of the Qiongdongnan Basin comprises three depositional units: submarine fan, feeder channel, and Semi-deep marine to deep marine mudstone. The submarine fan is a fan formed by the coupling and convergence of submarine fans sourced from the southwest and southeast. Internally, it is divided into three sub-facies: the proximal fan of the sand-rich submarine fan, the main body of the sand-rich submarine fan lobes, and the distal lobes of the sand-rich submarine fan. The submarine fan sourced from the southwest extends nearly north-south and is primarily fed by sediment transported through three large, banded ancient valleys. The sedimentary filling is characterized by three-phase progradation. The submarine fan sourced from the southeast extends nearly east-west and is primarily fed by sediment transported through a single large, banded ancient valley. The sedimentary filling is characterized by two-phase lateral accumulation. During the deposition period of the Sanya Formation, certain areas of the southern uplift belt were exposed for extended periods and subjected to weathering and erosion. Sediments are transported to large ancient valleys through small supply channels. A large number of sediments were transported to the southern slope of the Changchang sag through the provenance channel system such as large ancient valleys and slope belts and deposited in the center of the sag. These make up a complete system of large ancient uplifts and submarine fan source-to-sink sedimentary systems.The sedimentary model is a lobed submarine fan controlled by semi-restricted ancient valleys and expansive basins.

The Middle Miocene lobe-shaped and band-shaped submarine fans in the Lingshui Sag, Qiongdongnan Basin: source-to-sink system, genesis and implication - Xingzong Yao; Congjun Feng; Hongjun Qu; Min Zhang; Daming Li (Acta Oceanologica Sinica, 2024)

Sedimentary geochemistry of the Weihe River sediments, Central China: implications for provenance and weathering - Xiaoxia Peng; Congjun Feng; Ling Guo (Arabian Journal of Geosciences, 2021)

Lithology and oil-bearing properties of tight sandstone reservoirs: Chang 7 member of Upper Triassic Yanchang Formation, southwestern Ordos Basin, China - Congjun Feng; Hua Yang; Renhai Pu; Yaning Wang; Daxing Wang; Xiaowei Liang; Mengbo Zhang; Yougen Huang; Shixiang Fei (Geosciences Journal, 2017)

Control of petroleum traps by Cenozoic tectonic style in the Liaodong Bay area, of the Bohai Bay basin, China - Mengsi Sun; Chiyang Liu; Shuping Chen; Congjun Feng; Lei Huang (Arabian Journal of Geosciences, 2016)